Comparative Study of Coffee Wood and Fern Board Planting Media on Phalaenopsis amabilis Vegetative Growth in the Seedling Phase - Sari, Gita Maylita; Ulfah, Maria; Mulyaningrum, Eko Retno (BIOEDUSCIENCE, 2024)
Background: Phalaenopsis amabilis, or the moon orchid, is a popular type of orchid with high market demand. Planting media is a factor that can be successful in caring for the Phalaenopsis amabilis, which is an epiphytic orchid type or attaches to other plants. Most orchid planting techniques have not been adapted to their natural habitat in nature that attaches to other plants. The planting medium generally used for epiphytic orchids such as Phalaenopsis amabilis is fern boards, which are limited in nature. Researchers see the potential for coffee wood. Many can be used as a planting medium for Phalaenopsis amabilis because this plant is also found growing naturally in coffee plants. Methods: The research used comparative studies between coffee sticks and fern boards as planting media for Phalaenopsis amabilis on their vegetative growth according to their natural habitat by attaching to other plants. The analysis results were obtained by statistical tests t–test unpaired) using SPSS. Results: The analysis showed p ≤ 0.05 on the four parameters of Phalaenopsis amabilis growth. There are differences in the use of planting media types of coffee logs (M1) and fern boards (M2) on the vegetative growth of Phalaenopsis amabilis orchid plants, including the number of leaves, leaf span, leaf width, and root length. Conclusions: The vegetative growth on M1 and M2 is significantly different. The fern board planting media (M2) tends to be more recommended for use. After all, it can be optimal in providing vegetative growth consisting of the number of leaves, leaf span, leaf width, and root length because its growth is more stable.